Randomised Comparative Study of Nalbuphine Propofol Versus Fentanyl-Propofol for Proseal Laryngeal Mask Airway Insertion - Abhilasha Gupta; Ajay Gupta; Mukta Jitendra; Shruti Gupta (Dr. Annil Mahajan, 2022)
Background: The purpose of the study was to compare the Proseal laryngeal mask airway (PLMA) insertion conditions and haemodynamic changes by using either Nalbuphine-propofol or Fentanyl-propofol. Material and Methods: 60 ASA Grade 1 and 2 patients of age group 20-60 years, scheduled for general anesthesia were randomly allocated in two groups of 30 each. Group N received Nalbuphine 0.2mg/kg i.v and Group F received Fentanyl 2mcg/kg. Assessment of LMA insertion was done using 6 variables: resistance to mouth opening, gagging, swallowing, head and limb movements, laryngospasm and resistance to insertion. Incidence and duration of apnea were recorded. Patient's cardiorespiratory parameters, postoperative sedation score and complications if any were recorded. Results: The demographic profile was comparable in all the groups. The incidence of coughing /gagging was higher in group F as compared to group N (p=0.031). Swallowing was also statistically significant (p=0.034), being higher in group N as compared to group F. Limb movements followed the same pattern being higher in group F compared to group N (p=0.032). Laryngospasm was not seen in both the groups. The apnea duration was more in group F as compared to group N and was statistically significant (p<0.001). There was statistically significant Rise in heart rate and MAP in group F as compared to group N at 1st and 3rd minute. After PLMA insertion postoperative complications were statistically insignificant. Conclusion: The use of Nalbuphine-Propofol combination provides better PLMA insertion conditions with greater haemodynamic stability as compared to Fentanyl-propofol combination.